Towards efficient energy management in smart grids considering microgrids with day-ahead energy forecasting - Aslam, Sheraz; Khalid, Adia; Javaid, Nadeem (My University, 2020)
This study proposes an efficient energy management method to systematically manage the energy consumption in the residential area to alleviate the peak to average ratio and mitigate electricity cost along with user comfort maximization. We developed an efficient energy management scheme using mixed integer linear programming (MILP), which schedules smart appliances and charging/discharging of electric vehicles (EVs) optimally in order to mitigate energy costs. In the proposed model, consumer is able to generate its own energy from microgrid consisting of solar panels and wind turbines. We also consider an energy storage system (ESS) for efficient energy utilization. This work also performs energy forecasting using wind speed and solar radiation prediction for efficient energy management. Moreover, we perform extensive simulations to validate our developed MILP based scheme and results affirm the effectiveness and productiveness of our proposed energy efficient technique.
Keywords: Artificial neural network; Efficient energy utilization; Energy forecasting; Home energy management; Mixed integer linear programming; Renewable energy generation